Homosexuality & civilization - Crompton, Louis, 1925-2009 (Belknap Press of Harvard University Press, 2003)
"How have major civilizations of the last two millennia treated people who were attracted to their own sex? In a narrative tour de force, Louis Crompton chronicles the lives and achievements of homosexual men and women alongside a darker history of persecution, as he compares the Christian West with the cultures of ancient Greece and Rome, Arab Spain, imperial China, and pre-Meiji Japan."--Jacket